Review paperBiological indications of a novel “short” µ opiate receptor in domestic chicken - Sheehan, Melinda H.; Kream, Richard M.; Stefano, George B. (Archives of Medical Science, 2010)
Previous work from our laboratory has established that cellular signaling processes of endogenous morphine are mediated by cognate G protein coupled receptor (GPCR) proteins, designated µ3 and µ4 opiate receptors. µ3 and µ4 opiate receptors are structurally unique “short” 6 transmembrane helical (TMH) domain GPCRs that are selectively responsive to endogenous morphine, not to families of endogenous opioid peptides, and are uniquely coupled to activation of constitutive nitric oxide synthase (cNOS). Based on high resolution predictive measures, it appears likely that domestic poultry express a µ opiate receptor mRNA encoding potentially two novel GPCRs with similar biochemical characteristics as described for µ3 and µ4 opiate receptors as well as traditional µ1 opioid receptors. The biological indications of these novel µ opiate receptors are discussed within the context of this short review.